2006
DOI: 10.1111/j.1365-2265.2006.02576.x
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells as potential adjuvant for immunotherapy in adrenocortical carcinoma

Abstract: Our data demonstrate that autologous dendritic cells induce antigen-specific Th1 immunity in adrenocortical carcinoma. The clinical outcome, however, was not improved in the patients studied here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Therefore, these data await confirmation by others. In our studies, we were able to demonstrate that DCs might be fused with the tumour cells shown to have high efficacy rates in adrenal carcinoma cells (Papewalis et al 2006). Using electron microscopy, we could demonstrate viable cells indicated by intact basal membranes.…”
Section: Loading Methods In Tumour Antigensmentioning
confidence: 54%
See 1 more Smart Citation
“…Therefore, these data await confirmation by others. In our studies, we were able to demonstrate that DCs might be fused with the tumour cells shown to have high efficacy rates in adrenal carcinoma cells (Papewalis et al 2006). Using electron microscopy, we could demonstrate viable cells indicated by intact basal membranes.…”
Section: Loading Methods In Tumour Antigensmentioning
confidence: 54%
“…Recently, we also performed a DC vaccination trial in two patients with adrenocortical carcinoma (Papewalis et al 2006). Within this study, the mature DCs were generated as previously described (Schuler-Thurner et al 2002).…”
Section: Immunotherapy In Non-thyroid Endocrine Malignanciesmentioning
confidence: 99%
“…Mitotane is the only FDA-approved cytotoxic treatment, which has minimal effects on 5-year survival rates (Aufforth & Nilubol 2014). Immunotherapy approaches have not been successful due to the secretion of immunosuppressive glucocorticoids, the lack of known ACC-tumour-specific antigens and insufficient knowledge of the ACC immunosuppressive microenvironment (Papewalis et al 2006). In addition, adrenal masses are often clinically unapparent and with few reliable markers, histological differentiation of benign and malignant lesions remains difficult (Mansmann et al 2004).…”
Section: Adrenalcortical Tumourmentioning
confidence: 99%
“…The rationale of immunotherapy is based on the stimulation of the immune system against antigens of the neoplastic cell. The attempt to -stimulate the immune system‖ with autologous dendritic cells of two patients with ACC metastatic secreting induced antigen-specific Th1 immunity did not produce any clinical benefit [176]. Probably, the main limitation in this type of approach consists in the identification of a specific tumor antigen.…”
Section: Targeted Therapiesmentioning
confidence: 99%